2014
DOI: 10.3892/etm.2014.1839
|View full text |Cite
|
Sign up to set email alerts
|

In vitro damage of Candida albicans biofilms by chitosan

Abstract: With the increasing usage of indwelling medical devices in clinical practice, the frequency of fungal infections has increased, such as that of Candida albicans (C. albicans). Biofilms, a protected niche for microorganisms, are resistant to a range of current antifungal agents. Chitosan is a polyatomic biopolymer with advantageous biocompatibility, biodegradation, nontoxicity and antibacterial properties. To investigate the inhibitory effect of chitosan on biofilms formed by C. albicans, cell viability, 2,3-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…Coverslips were pretreated with concentrated sulphuric acid, 95% ethanol and foetal bovine serum prior to biofilm formation (Pu et al 2014). Formed biofilms were fixed with 2.5% glutraldehyde for 2 h and serially dehydrated with ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Coverslips were pretreated with concentrated sulphuric acid, 95% ethanol and foetal bovine serum prior to biofilm formation (Pu et al 2014). Formed biofilms were fixed with 2.5% glutraldehyde for 2 h and serially dehydrated with ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan has been previously confirmed to exhibit high activity against C. albicans and to act on the prevention and disruption of biofilms of C. albicans [25,41,42,43]. It has also been reported that C. albicans biofilms are resistant to commonly used antifungal agents such as fluconazole [44,45]; therefore we expected our chitosan-containing liposomes to act on C. albicans inhibition and express potent antifungal activity.…”
Section: Resultsmentioning
confidence: 91%
“…In addition to its wide use in conventional dosage forms, chitosan has also been extensively studied as a constituent in nanosystems, such as chitosan-based nanoparticles or nanoemulsions, or as a coating material for liposomes [16,17,18,19,20,21,22]. We were particularly interested in the fact that chitosan exhibits potent antimicrobial, particularly antifungal, effects [23,24,25]. Chitosan was able to disrupt the biofilm integrity and exhibited antifungal activity against Candida species [26] or bactericidal effects against Pseudomonas aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…Among the Candida species, Candida albicans (C. albicans) is responsible for 50-70% of cases of invasive candidiasis in the majority of clinical settings (1,2). C. albicans, an opportunistic fungal pathogen that normally inhabits the mucous membranes of the gastrointestinal and female genital tracts (3), is able to attack the immunocompromised patients (4). When the normal microbial barrier is disrupted, C. albicans can invade the intestinal and female genital mucosal barriers and causes candidiasis and candidemia (5,6).…”
Section: Introductionmentioning
confidence: 99%